Anterolateral vaginal cyst in an adult woman: a rare case of Mullerian cyst - Kalra, Ruchi; Gaur, Rajesh; Ali, Maryam; Ahmed, Nishat; Bhumija; Sharma, Sushil K.; Purohit, Tonushree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Mullerian cysts are of embryological origin and are usually found incidentally during delivery or a routine gynaecological examination. They remain asymptomatic unless they become large enough to cause heaviness or pressure on the surrounding structures, here we are presenting case of 29-year-old multi para (P2L2 both NVD) with 4×3 cm mass arising from the anterior vaginal wall. Complete vaginal cyst excision done. The cyst was filled with grey brown solid homogenous material and histopathology of ciliated columnar epithelium with squamous epithelium later on confirmed the diagnosis.